CREATING MODERN EVERYDAY SUITS BASED ON THE STUDY OF THE FEATURES NATIONAL FABRIC OF FERGANA VALLEY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the national costumes of women in the Fergana Valley, analyzes the fabrics used, the physical, mechanical and operational properties of materials, as a result of which a new line of modern women's clothing of complex shape was created.